From Colonial Epic to Modern Cultural Nationalism. Ollantay Travels Through South America - Fernández, Cristina Beatriz (2023)
The objective of this article is to review some rewritings of the central plotline of the famous Quechua drama Ollantay. It finds one of its earliest formulations in the epic poem Armas Antárticas, written by Juan de Miramontes y Zuázola in Peru at the beginning of the seventeenth century and reaches the discursive operations of cultural nationalism in modern Argentina, in the writings of Ricardo Rojas. In all cases, a resignification of the narrative material is evident, associated with both formal transformations and the symbolic needs of different socio-historical contexts. As is often the case with textualized materials in the so-called «indigenous literatures», the story starring Curricoyllor and Ollanta (or their various avatars) periodically bursts into the continuum of South American letters, forming variations of a common language, with mythical projections.